Two-way impact: Institutional e-learning policy/educator practices in creative arts through ePortfolio creation - Blom, Diana; Rowley, J.; Bennett, Dawn; Hitchcock, M.; Dunbar-Hall, P. (European Conference on e-Learning, 2013)
While tertiary institutions in Australia are embracing e-learning and urging, or making compulsory, some use by academics, it is often the educators themselves who engage with innovative e-learning approaches. These approaches, in turn, influence others in the institution and the institution’s thinking on e-learning. This paper focuses on the introduction or extension of ePortfolio usage into four creative arts departments in Australian universities. Each creative arts educator adopted the ePortfolio for a different purpose – music performance, theatre performance, music technology, music teacher training, professional writing - and in doing so has influenced, or at least is being monitored by, their university. All four projects have resulted in growth, development and enrichment of teaching and learning because of the ePortfolio’s facility to engage students in such activities as reflection, ongoing student-teacher dialogue, collaborative essay writing, peer evaluation, identity formation, long-term career planning, and, in doing so, to influence institutional curriculum design and e-learning policy.The researchers wanted to assess the use of ePortfolio for creative arts students in how they could appropriately document skills, competencies and graduate attributes learnt during their degree programs for career readiness. Literature notes institutional interest in ePortfolios for purposes including career preparation (Reese and Levy, 2009); demonstrating and assessing student learning (Jafuri, 2004); academic advising (Reese and Levy, 2009); and addressing public accountability concerns (Lorenzo and Ittelson, 2005a) by facilitating internal and external departmental review and accreditation (Reese and Levy, 2009). Within the four creative arts departments of our study the two-way impact between institution and educator is discussed. The findings of this study will inform future development of curriculum, policy and practice for creative arts students and academics in a variety of tertiary institutions. ePortfolios provide an efficient and transparent means to archive and access student work, and facilitate internal and external departmental review and broader institutional assessment.